PENERJEMAHAN UNGKAPAN TABU DALAM FILM THE BIG 4 KE DALAM BAHASA BELANDA - Fadiyah, Alfiyyah; Sutanarihesti, Triaswarin (UI Scholars Hub, 2025)
This study analyzes the occurrence of taboo expressions and their translation strategies into Dutch in the movie The Big 4. The research method used in this study is descriptive qualitative method. The analysis in this study uses theories related to the category of taboo expressions from Wardhaugh (2006) and Allan & Burridge (2006), then the theory of translation strategies of taboo expressions from Davoodi (2009). The results show that the categories of taboo expressions that appear the most from 129 data found in The Big 4 movie are animal names (45.7%), body parts (16.3%), sex (10.9%), mental abnormality (9.3%), death (7.8%), excretion (7.8%), and spirits (2.3%). The most common translation strategies applied by the translators are taboo to taboo (75.2%), censorship (14.7%), and substitution (6.2%). This shows the translators' tendency to maintain the emotional effect in the movie.